(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The combination of properties of Al/SiC composites make them very attractive materials for applications in automotive and aerospace industries. Several techniques are used in developing Al/SiC composites but stir casting process is most commonly used because it is the simplest and cost effective technique. However, composites produced via stir casting suffer from limitations such as low wettability and inadequate bonding between the molten Al & SiC particulates and the formation of degrading interfacial products like aluminum carbide (Al4C3) which degrades the mechanical properties of the composite. Some of the techniques to improve Al-SiC wettability include addition of surface active elements such as magnesium, heat treatment of particles and application of metallic coating on the reinforcements before addition to the melt. Wetting agents alter the composition of the matrix alloy, while heat treatment of the reinforcement does not completely prevent the formation of Al4C3 when utilized. To reduce the direct interaction and promote wetting between reinforcements and molten aluminum during processing, the surface of SiC particulates can be modified by coating via oxidation, sol-gel and electroless processes. Of all these methods, electroless nickel deposition produces the best coatings with uniform thickness and adequate strength. In the present study, influence of electroless nickel-coating of SiC on the mechanical, corrosion and microstructural properties of Al/SiC composite has been evaluated. Finally, it can be concluded that the Ni and Ni3P intermetallic phases produced via electroless coating improves the wettability between the SiC and molten aluminium leading to enhanced properties of the composite.